Evaluating factors influencing Tennessee and Kentucky farmers’ willingness to sell produce through fresh stop markets - Denton, Riley; Velandia, Margarita; Yenerall, Jackie; DeLong, Karen; Trejo-Pech, Carlos; Chen, Xuqi; Tanaka, Keiko; Rignall, Karen; Schexnayder, Susan (Frontiers in Sustainable Food Systems, 2023)
TIntroduction: The food justice movement focuses on resolving food system inequalities, including, but not limited to, income, ethnicity, and race differences related to household access to food, farmer access to markets, and the fair treatment of farmworkers. Previous studies have focused on food system inequalities from the consumer demand side, but only a few studies have focused on the role farmers play in creating more equitable food systems. An example of a market model aiming to fulfill various missions of the food justice movement is Fresh Stop Markets (FSMs). FSMs aggregate food from local farmers and sell shares on a sliding scale based on consumers’ income. Lower income households pay less than higher-income households for the same food. A vital component of this market concept is farmers’ willingness to sell produce through FSMs. Methods: We used data from a 2020 survey of Tennessee and Kentucky fruit and vegetable farmers and the double-bounded dichotomous choice contingent valuation approach to assess farmers' willingness to sell produce through FSMs when faced with a price discount scenario. A probit regression was used to investigate the factors correlated with farmers’ willingness to sell produce through FSMs Results and Discussion: Results suggest gross farm revenue, farmer age, education, experience selling produce through farmers markets, and running programs on the farm to educate communities about sustainable agriculture and food systems are associated with farmers’ willingness to sell produce through FSMs. Conclusions: Farmer and farm business characteristics, as well as prior experience running education programs on the farm related to sustainable agriculture and food systems, are important factors to consider when trying to engage farmers willing to sell produce through FSMs.